Effect of Drill Method Application on Short Serving Accuracy and Eye-Hand Coordination in Badminton Game - Shinta Tri Astuti; Meirizal Usra; Sri Sumarni; Iyakrus Iyakrus; Wahyu Indra Bayu (Universitas PGRI Palembang, 2022)
The purpose of this study was to determine whether there is an effect of applying the drill method with short serve accuracy and eye-hand coordination on badminton games. The method used is the experimental method with a one group pretest and posttest design. The subjects in this study were all 35 students of SMA Plus Al-Hannan. To take the sample using the test of homogeneity, normality, and hypothesis t test. in this study indicate that the results of the initial test and the resulting final test are normality and homogeneity tests, the results of the distribution data are normal and homogeneous. Then test the t-test hypothesis. H0 is accepted if significant > 0.05 and H0 is rejected otherwise, so it is stated that for hypothesis testing I obtained tcount = 14.738 with a significant level <0.05 so that there is an effect of drill practice on the accuracy of short serve badminton games for SMA PLUS Al-Hannan students. South OKU. Thus, testing hypothesis II, obtained tcount 22.148 with a significance level of <0.05 that there is an effect of drill practice on eye-hand coordination of students of SMA Plus Al-Hannan OKU Selatan. Based on the results of the research data above, it can be said that the drill method has a significant effect on the accuracy of badminton service and eye-hand coordination in students of SMA PLUS Al-Hannan OKU Selatan.